Collaboration Process, Inhibiting and Supporting Factors in the Proactive Recruitment Program for Candidate Members of the Republic of Indonesia Police - Samad, Fadly; Haning, Muh. Thahir; Ibrahim, Muh. Akmal; Iskandar, Didik (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the collaboration process and inhibiting and supporting factors in collaborative innovation in the proactive recruitment program for prospective members of the Indonesian National Police. The research design used is qualitative with a case study strategy. This research was conducted at 3 Regional Police (POLDA), namely the South Sulawesi Police, North Kalimantan Police, and Papua Police. Determination of research informants using purposive sampling. Data collection includes observation, in-depth interviews, and document reviews. Data analysis techniques use interactive data analysis. Validity and reliability use triangulation, combining various data sources, methods, or theories to verify and strengthen research findings. The results of the research on the process in the Proactive Recruitment Program involve complex collaboration between internal and external stakeholders, with major challenges such as limited access to information in remote areas, lack of coordination, and administrative barriers. The driving factors include competent human resources, good cooperation, and technology, while the obstacles are problems with coordination, infrastructure, data incompatibility, and social and cultural challenges.